Spatiotemporal Evolution of Intense Short Gaussian Laser Pulses in Weakly Relativistic Magnetized Plasma. Issue 2 (February 2016) - Olumi, M.; Maraghechi, B.
Abstract: The weakly relativistic regime of propagation of a short and intense laser pulse in the magnetized plasma is investigated. By considering relativistic nonlinearity and using non‐linear Schrödinger equation with paraxial approximation, two second‐order coupled differential equations are obtained for the longitudinal pulse width parameter (in time) and for the transverse pulse width parameter (in space). The simultaneous evolution of spot size and length of a relativistic Gaussian laser pulse in a magnetized plasma can be calculated by the numerical solution of the equations. The effect of magnetic field is investigated. It is observed that in the presence of magnetic field both the self‐compression and the self‐focusing can be enhanced. Furthermore, the interplay between the longitudinal self‐compression and the transverse self‐focusing in a magnetized plasma is investigated. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)